2014
DOI: 10.1093/nar/gku441
|View full text |Cite
|
Sign up to set email alerts
|

Force-induced melting of DNA—evidence for peeling and internal melting from force spectra on short synthetic duplex sequences

Abstract: Overstretching of DNA occurs at about 60–70 pN when a torsionally unconstrained double-stranded DNA molecule is stretched by its ends. During the transition, the contour length increases by up to 70% without complete strand dissociation. Three mechanisms are thought to be involved: force-induced melting into single-stranded DNA where either one or both strands carry the tension, or a B-to-S transition into a longer, still base-paired conformation. We stretch sequence-designed oligonucleotides in an effort to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 40 publications
3
40
1
Order By: Relevance
“…Laser-tweezers force-spectroscopic data (Bosaeus et al 2012(Bosaeus et al , 2014) on short DNA of variable sequence are here used as basis for discussing the structural and energetic properties of Σ-DNA and to put forward a disproportionation hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser-tweezers force-spectroscopic data (Bosaeus et al 2012(Bosaeus et al , 2014) on short DNA of variable sequence are here used as basis for discussing the structural and energetic properties of Σ-DNA and to put forward a disproportionation hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The Σ-form may be considered a special case of the wider group of stretched DNA forms that have been called 'S-DNA' some of which, though, appear less well defined. In contrast to the Σ-form observed for base-paired GC-rich DNA stretched along the 3′-3′ ends, S-DNA is usually observed as a 70% elongated form when stretching a long plasmid or phage DNA (Cluzel et al 1996;Williams et al 2002) and, at least in AT-rich DNA, S-DNA appears to involve denaturation (Bosaeus et al 2012(Bosaeus et al , 2014. The fact that the Σ-form has so long escaped discovery is thought to be due to that it is first recently stretch experiments on short synthetic DNA have been possible with high accuracy (Bosaeus et al 2012(Bosaeus et al , 2014.…”
Section: Introductionmentioning
confidence: 91%
“…Simulations have shown that whereas G-C pairs persist through the transition, A-T pairs often form melted bubbles (30,37). Similarly, various pulling experiments and theoretical models have also demonstrated that at low-to-moderate monovalent salt conditions (<150 mM), AT-rich sequences tend to melt more easily than GC-rich sequences (24,28,29,(65)(66)(67)(68)(69), whereas under high-salt conditions interstrand charge repulsion is reduced, and AT-rich sequences also form S-DNA (31,32). Moreover, cyclic pulling experiments demonstrate that force-induced melting is associated with hysteresis, such that once melted, the complementary strands reanneal slowly (21,28,32,70).…”
Section: High-force Regime: Dap Substitution Decreases the Tension Atmentioning
confidence: 98%
“…The pathway by which DNA becomes overstretched is a function of local stability and is determined by buffer conditions and sequence (26,27). Experiments using relatively short sequences have demonstrated that in physiological salt conditions, AT-rich regions tend to denature upon overstretching, whereas GC-rich regions remain hybridized (28,29). Similarly, molecular dynamic simulations suggest that stronger base pairing in GC-rich regions maintains base registration and minimizes interstrand separation, producing a higher transition force (30).…”
Section: Introductionmentioning
confidence: 99%
“…36 At the low-salt conditions used in these experiments, this transition occurs at about 62 pN and represents a conversion of DNA from dsDNA to ssDNA as the DNA is destabilized by force and primarily peels from its free end. [37][38][39][40][41][42] The force-extension profiles of ssDNA and dsDNA cross at $6 pN [ Fig. 1(B)].…”
Section: Pol III Core Activity At Constant Forcementioning
confidence: 99%